CHARACTERISTICS OF PRERENAL AND RENAL INJURY IN NEONATAL AGE - Naunova-Timovska Silvana (Medical Faculty, Ss. Cyril and Methodius University in Skopje, 2015)
Objective Pre-renal injury is the most common type of acute kidney injury in newborn infants. It occurs in over 80% of cases, as a result of inadequate renal perfusion. Renal injury appears due to parenchymal kidney damage. The aim of the study was to analyze the demographic characteristics of prerenal and renal injury in neonates. Materials and Methods: In this clinical, prospective study over a period of 3 years (January 2012 - December 2014) 50 infants with documented acute kidney injury were evaluated. The patients were hospitalized in the intensive care unit at the Children's University Hospital. Medical data records of admitted neonates with kidney injury were analyzed. The material was statistically processed using methods of descriptive statistics. Results: A totol of 770 neonates, we evaluated 50 neonates with documented acute kidney injury who at the period of 3 years were treated in NICU. The incidence of kidney injury was 6.5%. Pre-renal injury was observed in 39/50 infants and renal injury in 11/50 infants. The prevalence of pre-renal injury was 78% and 22% of renal injury. Most of involved neonates were term and male. The most common comorbid condition in infants with pre-renal AKI was perinatal asphyxia observed in 41% of cases and prematurity with respiratory distress observed in 36% of infants with renal AKI. Mortality rate was 33% in prerenal AKI and it was highest in patients with perinatal asphyxia. While the mortality rate of renal AKI was 45% and it was highest in the group of infants with congenital heart anomalies. Conclusion: Acute kidney injury is a serious condition which damages the kidney as a central mediator of the homeostasis of bodily fluids. Pre-renal injury is the most common type of neonatal AKI. Timely and adequate treatment of renal hypoperfusion leads to improvement of renal function.
Keywords: prerenal kidney injury; renal kidney injury; newborn infants